Assessment of quality of life in Indian patients with vitiligo, an observational study - Trivedi, Vedang D.; Rana, Devang A.; Thakkar, Kandarp K.; Malhotra, Supriya D. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Vitiligo is the most common hypopigmentary disorder. In India, the incidence of vitiligo is 0.25-2.5%. It considerably influences the patient’s quality‑of‑life (QoL) and psychological well‑being. Methods: A prospective, observational study was conducted from April 2016 to September 2016 in dermatology outpatient department. Patients clinical characteristic were noted and Quality of life was assessed by using Vitiligo Quality of Life Questionnaires [VQLQ]. During item development, none of the questions were changed according to the results of cognitive and understand ability testing. The scale consisted of 25 questions. The answer to each question was scored as ‘never = 1’, ‘sometimes = 2’, ‘often = 3’ and ‘all the time = 4’, so the total score ranged between 25 and 100. Higher scores represented more severely impaired quality of life. Results: We enrolled 78 Vitiligo patients who were attending dermatology department for phototherapy. Out of them 53 were female. Mean age was 37.12±12.270. Most common age group was 31-40 years. Mean VLQL score 40.92±6.081. Patients were divided based on VQLQ score in Moderate (50-75) and Low score group (25-50). Vitiligo patients presented with symptoms of pain, irritation and itching (P<0.0001). Vitiligo patients when assessed for feeling domain were significantly embarrassed for their overall look and appearance. (P < 0.0001). When Personal relationship domain was analysed physical contact was a major concern (P <0.002). Patients suffering from Vitiligo were significantly worried about spread of vitiligo and occurrence of cancer (P<0.0001). Therapy for Vitiligo was time consuming time and was a work place challenge for the patients (P <0.0001). The reliability of VQLQ in our study was Cronbach’s α coefficient was 0.876. Conclusions: QoL impairment was relatively high in vitiligo patients. Medical intervention and counselling should focus to improve feelings, personal relationship, anxiety, school/work, leisure and symptom domains.